A case study evaluation of implementation of a care pathway to support normal birth in one English birth centre: anticipated benefits and unintended consequences - Rycroft-Malone Jo; Bick Debra E; Fontenla Marina (BMC, 2009)
Abstract Background The policy drive for the UK National Health Service (NHS) has focused on the need for high quality services informed by evidence of best practice. The introduction of care pathways and protocols to standardise care and support implementation of evidence into practice has taken place across the NHS with limited evaluation of their impact. A multi-site case study evaluation was undertaken to assess the impact of use of care pathways and protocols on clinicians, service users and service delivery. One of the five sites was a midwifery-led Birth Centre, where an adapted version of the All Wales Clinical Pathway for Normal Birth had been implemented. Methods The overarching framework was realistic evaluation. A case study design enabled the capture of data on use of the pathway in the clinical setting, use of multiple methods of data collection and opportunity to study and understand the experiences of clinicians and service users whose care was informed by the pathway. Women attending the Birth Centre were recruited at their 36 week antenatal visit. Episodes of care during labour were observed, following which the woman and the midwife who cared for her were interviewed about use of the pathway. Interviews were also held with other key stakeholders from the study site. Qualitative data were content analysed. Results Observations were undertaken of four women during labour. Eighteen interviews were conducted with clinicians and women, including the women whose care was observed and the midwives who cared for them, senior midwifery managers and obstetricians. The implementation of the pathway resulted in a number of anticipated benefits, including increased midwifery confidence in skills to support normal birth and promotion of team working. There were also unintended consequences, including concerns about a lack of documentation of labour care and negative impact on working relationships with obstetric and other midwifery colleagues. Women were unaware their care was informed by a care pathway. Conclusion Care pathways are complex interventions which generate a number of consequences for practice. Those considering introduction of pathways need to ensure all relevant stakeholders are engaged with this and develop robust evaluation strategies to accompany implementation.